RGO enveloped vertically aligned Co3O4 nanowires on carbon fabric: a highly efficient prototype for flexible field emitter arrays. Issue 94 (28th September 2016) - Howli, Promita; Das, Swati; Saha, Subhajit; Das, Biswajit; Hazra, Partha; Sen, Dipayan; Chattopadhyay, Kalyan Kumar
Abstract : RGO enveloped Co3 O4 nanowires on flexible carbon fabric exhibit a splendid field emission performance with remarkably enhanced current density. Abstract : A surfactant-free new approach is formulated for synthesizing Co3 O4 nanowires on a flexible carbon fabric substrate by a simple chemical route. The devised protocol yields uniform and highly dense nanowire distributions that are able to sustain their structural and morphological integrities even under severe bending and twisting. To understand the growth process of these Co3 O4 nanowires on the chemically activated carbon fabric, the morphological evolutions are investigated in a step-by-step manner using FESEM and HRTEM analysis. As-synthesized Co3 O4 nanowires, endowed with sharp edge features of their morphology, are found to exhibit excellent p-type field emitting traits with a very low turn on field of 0.86 V μm −1 with a significant current density of ∼0.5 mA cm −2 at a relatively lower applied electric field of ∼1.4 V μm −1 . To improve the current density and field enhancement factor even further, RGO sheets are anchored over the Co3 O4 nanowires so that the conducting RGO sheets could potentially enrich the field emission performance due to its high electron affinity. Thus the designed hybrid nanostructures are found to display a turn-on field of 0.8 V μm −1 and current density twice (1 mA cm −2 ) that of bare Co3 O4 nanowires. Experimental observations indicate that these hybrid RGO wrapped Co3 O4 nanostructures are highly promising as cold cathodes in flexible field emission display applications.